Experience with trans radial uterine artery embolisation for uterine fibroids in a tertiary center in Saudi Arabia - Farid, Gehan; Kamal, Reem; Al-Shammari, Mohammed Thani; Swaraldahab, Mohamed; Swaraldahab, Hassan (Clinical Journal of Obstetrics and Gynecology, 2020)
Trans-radial uterine artery embolization (UAE) is acknowledged as a non- invasive, cost-effective and safe procedure for the treatment of symptomatic fibroids. However, it is associated with the recurrence of symptoms like abnormal uterine bleeding and pressure symptom in some patients. This is a comparative study of our data with other international data, in the context of percentage reduction in fibroid size, accompanying controlling factors, short and long term follow up data analysis of the first two years was done. Careful pre-procedural counseling of future possibility of fibroid recurrence and means of management should be stressed. Materials and methods: A retrospective cohort study at the Security Forces Hospital in Riyadh, Saudi Arabia, was conducted. The study was done from 1st November 2017-31st October 2019, on symptomatic patients diagnosed with fibroids, who refused surgical treatment. The outcomes included: fibroid site, size and anatomical position, patients’ symptoms, general condition, and early and delayed complications. These data were compared with those from other international studies. Results: The study involved 23 patients (mean age: 39 years). The average percentage reduction in fibroid volume was 49%. There were no major complications and no recurrence of symptoms during the covered period. Data analysis revealed a poor correlation between the overall percentage reduction of fibroid size with fibroid number, age of patients’, and body mass indices. Conclusion: Despite poor correlation, we provided preliminary data of the first two years out of the total five-year projected period of the study where it showed effectiveness and relative safety of radial - UAE for fibroid.